Factors Association with Needle Stick Injury: An Overview of Prevention & Management - Aljameeli, Ohud Matar; Alrasheedi, Norah Mudlah; Alsuhali, Amsha Mohammad; Alsuhali, Sarah Mohammad; Alsuhali, Dhawwaa Mohammad (International Journal of Innovative Research in Medical Science, 2022)
Background: Every day, almost 20 million committed health care workers (HCP) are exposed to biological, chemical, and mechanical risks. According to the World Health Organization, nearly three million health care personnel are exposed to blood and other fluids each year as a result of needle stick or sharps accidents. Needlestick and sharps injuries (NSIs) are among the most common job-related injuries suffered by health care professionals. In fact, one of the most common occupational dangers among health care workers is the transmission of hepatitis B or C through work-related NSIs. Methods: This is a review is based on collecting all previous articles which were done on Factors association with needle stick injury: An Overview of Prevention & Management. Results: The review process involved determining the suitability of 20 publications. There were 20 papers that made it through the full text screening and into the final review. The purpose of this research was to assess Factors association with needle stick injury: An Overview of Prevention & Management. Conclusion: The findings indicated that no single device, place, or behaviours can be held solely accountable for all types of NSIs, although each can contribute to the injury. HCWs must use safety equipment more frequently, and training institutions with constant observation for procedures to reduce NSIs must be designed and implemented.